Diagnostics and systemic treatment of triple-negative breast cancer: discoveries of the past, challenges for the future - Chmielewski, Grzegorz; Góźdź, Stanisław (Medical Studies/Studia Medyczne, 2024)
Despite decades of progress in providing breast cancer patients with the most effective treatment methods, successful management of triple-negative subtype of this neoplasm remains an unmet need of oncology. Molecular heterogeneity, immunological evasion mechanisms and genomic instability all contribute to this cancer’s troubling picture. Nevertheless, there have been substantial advances in exploration of the molecular landscape and innovative therapy of this entity. Discovery of molecular subtypes of triple-negative breast cancer has led to better understanding of the pathophysiological basis of the disease and gives hope for highly demanded personalized therapies. Work on targeted treatments is underway, including anti-Trop-2 antibodies, as well as PARP and PD-1/PD-L1 inhibitors. Efficacy of these drugs often relies on the presence of specific molecular targets; therefore there is a need for fast, affordable, and widely available molecular analysis methods. There is still a long road ahead, but with each discovery researchers are getting closer to making the diagnosis of triple-negative breast cancer less dire for the patient, with more effective tools at hand for the therapeutic team.